2013
DOI: 10.3727/096368911x582769b
|View full text |Cite
|
Sign up to set email alerts
|

The Immunosuppressive Effect of Mesenchymal Stromal Cells on B Lymphocytes is Mediated by Membrane Vesicles

Abstract: The immunomodulatory properties of mesenchymal stromal cells are the subject of increasing interest and of widening clinical applications, but the reproducibility of their effects is controversial and the underlying mechanisms have not been fully clarified. We investigated the transfer of membrane vesicles, a recently recognized pathway of intercellular communication, as possible mediator of the interaction between mesenchymal stromal cells and B lymphocytes. Mesenchymal stromal cells exhibited a strong dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…To elucidate if circulating microRNA-150 was encapsulated in exosomes, in microvesicles or in protein/lipid complexes, 15 CLL serums were centrifuged at 20,000g (to pellet microvesicles) and subsequently at 150,000g (to pellet exosomes) for 1 h at 4°C as previously described (25,26). Uncentrifuged, microvesicle-depleted and exosome-depleted sera were processed as described above to detect microRNA levels.…”
Section: Microvesicles and Exosomes Precipitationmentioning
confidence: 99%
“…To elucidate if circulating microRNA-150 was encapsulated in exosomes, in microvesicles or in protein/lipid complexes, 15 CLL serums were centrifuged at 20,000g (to pellet microvesicles) and subsequently at 150,000g (to pellet exosomes) for 1 h at 4°C as previously described (25,26). Uncentrifuged, microvesicle-depleted and exosome-depleted sera were processed as described above to detect microRNA levels.…”
Section: Microvesicles and Exosomes Precipitationmentioning
confidence: 99%
“…These authors observed a dose-dependent inhibitory effect of MSC-EVs on B-cell proliferation, differentiation and production of IgM, IgG and IgA, in a CpG-stimulated peripheral blood mononuclear cell culture system [68]. Moreover, it has been shown that MSC-EVs are internalized only in a subset of activated B lymphocytes CD19+/CD86+ [68].…”
Section: Immune-modulatory Capacities Of Evs Derived From Mscsmentioning
confidence: 94%
“…The effect of EVs obtained from human bone marrow MSCs on B lymphocytes has been investigated by Budoni et al [68]. These authors observed a dose-dependent inhibitory effect of MSC-EVs on B-cell proliferation, differentiation and production of IgM, IgG and IgA, in a CpG-stimulated peripheral blood mononuclear cell culture system [68].…”
Section: Immune-modulatory Capacities Of Evs Derived From Mscsmentioning
confidence: 97%
“…In animal and in vitro studies, MSC-derived extracellular vesicles restored Th1/ Th2 balance and induced generation of Tregs, implementing the regulatory component of the adaptive immune system [77,78]. A dose-dependent inhibitory effect of MSC-derived extracellular vesicles on B-cell proliferation, differentiation and Ig production has been reported [58]. In a mouse model of severe refractory asthma, MSC-derived extracellular vesicles were as potent as the MSCs themselves in mitigating allergic airway inflammation [79].…”
Section: Anti-inflammatory (M2) Mscs Inhibit the Cell Cycle Of Cytotmentioning
confidence: 96%
“…1). Some studies have suggested that MSCs can also inhibit B cell activation, proliferation, differentiation and chemotactic responses [58], although knowledge regarding MSC-mediated modulation of B cells is still limited (Fig. 1).…”
Section: Mscs As a Possible Regulator Of Neonatal Sustained Inflammationmentioning
confidence: 99%